PENINGKATAN KETERAMPILAN MEMBACA KALIMAT BERHURUF JAWA BERSANDHANGAN PANYIGEG MELALUI PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING PADA SISWA KELAS VII A SMP NEGERI 1 JATIROTO TAHUN PELAJARAN 2014/ 2015 - Herlambang, Nizar Raditya; Suyitno, Suyitno; Wijayanti, Kenfitria Diah (Universitas Sebelas Maret, 2017)
This research is aimed to: (1) explain the obstacles learning to reading skill of Java lettered sentences with sandhangan panyigeg in the class VII A of SMP Negeri 1 Jatiroto in the academic year of 2014/ 2015 and (2) describe the improvement of reading skill of Java lettered sentences with sandhangan panyigeg in the class VII A of SMP Negeri 1 Jatiroto in the academic year of 2014/ 2015 through cooperative learning type snowball throwing. This research carried out two cycles. Source data derived from informants, events, and documents/ archives. The technique of data collecting were used are from interview, observation, documentation, and test. Data validity used the technique of triangulation source. The technique of data analyzing were comparative descriptive analysis and critical analysis technique. The conclusion of the research is there would be some obstacles that occur in implementating of learning to reading skill of Java lettered sentences with sandhangan panyigeg. The implementation of cooperative learning type snowball throwing can improve reading skill of Java lettered sentences with sandhangan panyigeg in the class VII A of SMP Negeri 1 Jatiroto in the academic year of 2014/ 2015.